2015
DOI: 10.1177/0016986214568720
|View full text |Cite
|
Sign up to set email alerts
|

Even the Best Have Difficulties

Abstract: To achieve top scores, students need not only talents and study skills but also they have to conquer various adversities successfully. This research focused on the study paths, the concept adopted from Hickman, Bartholomew, Mathwig, and Heinrich (2008), of Finnish straight-A graduates in general upper secondary education. In this article, we refer to these paths with the concepts of study processes or just studies. The purpose was to analyze what kinds of difficulties these graduates had faced and how they cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Salmela and Määttä (2015) found in their study that straight "A" students found it difficult to maintain their high grades and have many friends. Peterson et al (2009) focused on negative life events of gifted students over an 11-year period.…”
Section: Relationships With Classmates (Sense Of Belonging)mentioning
confidence: 98%
“…Salmela and Määttä (2015) found in their study that straight "A" students found it difficult to maintain their high grades and have many friends. Peterson et al (2009) focused on negative life events of gifted students over an 11-year period.…”
Section: Relationships With Classmates (Sense Of Belonging)mentioning
confidence: 98%
“…Both low-achievers and high-achievers at school need teachers who express trust, appreciation, and caring toward students by their action and enthusiasm. These features help students to tolerate and manage burdensome studies, to recognize strengths in themselves to balance the performance-related demands, and to appreciate themselves and their achievements as they are (Salmela & Määttä, 2015;Salmela & Uusiautti, 2013;; see also Peterson, Duncan, & Canady, 2009. ) There are also interventions, such as the Penn Resiliency Programme (PRP) (Seligman, Ernst, Gillham, Reivich, & Linkins, 2009) and "You Can Do It!"…”
Section: Discussionmentioning
confidence: 99%
“…Students who are willing to study and interested in learning, such as straight-A graduates are (see Salmela & Määttä, 2015;Salmela & Uusiautti, 2013;, evaluate often positively their learning environments (Pulkka & Niemivirta, 2013). These students as high-achievers are significantly above the average students' grades.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching can also focus on children's strengths and talent, and promote their flourishing. The strength-based approach (Carman, 2005;Linkins et al, 2015;Salmela and Määttä, 2015;Salmela and Uusiautti, 2015;Seligman, 2015) aims this kind of flourishing and is based on research conducted within the field of positive psychology (Peterson and Seligman, 2004;Seligman et al, 2009;Bernard and Walton, 2011). Strength-based education thus leans on the idea that every human being has their signature strengths (e.g., perspective, perseverance, humanity, fairness, etc.)…”
Section: Conclusion: the Strength-based Approach As A Solution?mentioning
confidence: 99%